2017
DOI: 10.1371/journal.pone.0187581
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA profile of infantile hemangioma by microarray analysis

Abstract: BackgroundCircular RNAs (circRNAs) are a recently identified class of noncoding RNAs that participate in several physiological processes. However, the expression of circRNAs in infantile hemangioma (IH) remains unknown.MethodsThe profile of circRNAs was assessed by microarray in four pairs of IH and adjacent skin tissues. The expression of circRNAs was validated by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Furthermore, circRNA-microRNAs (miRNA)-mRNA networks were constructed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…[2] The pathogenesis of hemangioma has been widely studied, and several theories have been proposed, among which endothelial progenitor cell theory, Folkman Klagsbrun placental theory, angiogenesis theory, and hypoxia theory are the most accepted. [23] To date, circRNA profiles by microarray analysis in the IHs have been reported, [11] and 234 up- and 374 downregulated circRNAs were identified in IH by microarray. [11] In this study, based on the RNA-Seq technique, we found that 249 circRNAs are dysregulated in IH including 124 upregulated and 125 downregulated circRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[2] The pathogenesis of hemangioma has been widely studied, and several theories have been proposed, among which endothelial progenitor cell theory, Folkman Klagsbrun placental theory, angiogenesis theory, and hypoxia theory are the most accepted. [23] To date, circRNA profiles by microarray analysis in the IHs have been reported, [11] and 234 up- and 374 downregulated circRNAs were identified in IH by microarray. [11] In this study, based on the RNA-Seq technique, we found that 249 circRNAs are dysregulated in IH including 124 upregulated and 125 downregulated circRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…[23] To date, circRNA profiles by microarray analysis in the IHs have been reported, [11] and 234 up- and 374 downregulated circRNAs were identified in IH by microarray. [11] In this study, based on the RNA-Seq technique, we found that 249 circRNAs are dysregulated in IH including 124 upregulated and 125 downregulated circRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations